Upaya Meningkatkan Kemampuan Perencanaan Karier Melalui Layanan Informasi Karier pada Saat Pandemi Covid-19 bagi Siswa di SMA Negeri 2 Praya - Ni Nyoman Danti (Universitas Pendidikan Mandalika, 2021)
The purpose of this study was to improve career planning skills through career information services during the Covid-19 pandemic for class XII-MIA-1 students of SMA Negeri 2 Praya in the academic year 2020/2021. This research method uses a classroom action research method consisting of 2 cycles of action. The research instrument used observation sheets and tests. The data analysis technique used descriptive analysis. Based on the results of the data analysis of the implementation of the action in cycle I, it shows that the percentage of students' career planning abilities is very high as many as 4 people or 11.76%, high career planning abilities are 5 people or 14.71%, while as many as 8 people or 23.53% , low 8 people amounted to 23.53% and very low category career planning ability 9 people or 26.47%. Based on the results of cycle II analysis, it was found that students had very high career planning abilities as many as 12 people or 35.29 %%, high career planning abilities by 9 people or 26.47% and career planning abilities in the medium category of 7 people or 20.59%, low career planning ability as many as 4 people or 11.76%, and very low career planning ability as many as 2 people or 5.88%.